2021
DOI: 10.3390/app11199134
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pre-Tightening Torque Dependent Parameters for Empirical Modeling of Bolted Joints

Abstract: The vibration characteristics of bolted structures are crucially affected by the pre-tightening torque. An approach for identifying the pre-tightening torque dependent stiffness parameters of bolted joints is proposed in this paper. Firstly, the interface of the bolted joint is characterized by the thin layer element with the isotropic material property, and the parameter value of the property is assigned relative to the distance from the center of the bolt; the influence of the bolt is ignored. Secondly, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…It should be stated that in reality, the size of this angle (see Figure 5) can differ. Moreover, this angle is very important from a technical point of view and also serves as a basis for new calculation methodologies, e.g., see [5]. However, this issue will be described in more detail in Section 3.…”
Section: Description Of the Basic Approach To Solving Bolted Jointsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be stated that in reality, the size of this angle (see Figure 5) can differ. Moreover, this angle is very important from a technical point of view and also serves as a basis for new calculation methodologies, e.g., see [5]. However, this issue will be described in more detail in Section 3.…”
Section: Description Of the Basic Approach To Solving Bolted Jointsmentioning
confidence: 99%
“…In the following, the study of literature sources focused on existing theoretical calculation procedures, which are presented, e.g., in [3] and [4]. Attention was also given to new methods of calculations as reported by Y. Tian [5]. Previous research on the effect of the asymmetry of a multi-bolted connection on the asymmetry of the connected pressure vessel shell has also provided an important basis for solving the problem, see [6].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the nut rotation angle measured by the protractor is compared and analyzed with the detection value of YOLOv5; analysis of the experimental data is shown in Table 3. The error of bolt loosening angle is calculated by Equation (6).…”
Section: Identification Of Bolt Loosening At Any Anglementioning
confidence: 99%
“…The mechanical performance of the bolted connection is related to pretightening torque, thread pair contaction and friction of contact surfaces [ 6 , 7 , 8 ]. In order to explore the mechanism of bolt loosening, Goodier et al [ 9 ] tested the behavior of bolted connections under dynamic load.…”
Section: Introductionmentioning
confidence: 99%
“…At present, domestic and foreign scholars have done a lot of research on the theory of pipe joints and contact mechanics in the aviation hydraulic system, and found that the flarefree connection structure has the advantages of convenient connection, repeatable disassembly and assembly, good sealing performance, and so on. [1] Tian et al [2] proposed a method to determine the stiffness parameters related to the pretightening moment, which could obtain all parameters of equivalent thinlayer elements within a certain range of pretightening moment. Zheng et al [3] conducted repeatability experiments on threaded fasteners in the tightening process and found that the preload force and its loss had a large dispersion.…”
Section: Introductionmentioning
confidence: 99%